1998
DOI: 10.1159/000040856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Three Days Starvation on the Phagocytic Activity of Rat Peritoneal Macrophages

Abstract: To examine the effect of starvation on the phagocytic activity of rat peritoneal macrophages, 8 animals were kept for 3 days on water supply only. The cells showed an increased capacity for superoxide anion production and a marked decrease in their ability to engulf latex particles. The corticosterone level of the fasting animals was markedly increased, an observation suggesting that the alteration of macrophage function could be hormonally mediated. The findings in the present study indicate that the decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…De la Fuente et al (1992) observed impaired peritoneal macrophage function in mice fed a low-protein diet for 15 days. We have shown that the phagocytic activity of peritoneal macrophages from rats kept on water only for 3 days was decreased, whereas their ability to generate superoxide anion was markedly increased (Salman et al, 1998b). Since the serum corticosterone level of the fasting animals was found to be increased, it was suggested that the impaired macrophage function is hormonally mediated.…”
Section: Certain Conditions Affectingmentioning
confidence: 95%
“…De la Fuente et al (1992) observed impaired peritoneal macrophage function in mice fed a low-protein diet for 15 days. We have shown that the phagocytic activity of peritoneal macrophages from rats kept on water only for 3 days was decreased, whereas their ability to generate superoxide anion was markedly increased (Salman et al, 1998b). Since the serum corticosterone level of the fasting animals was found to be increased, it was suggested that the impaired macrophage function is hormonally mediated.…”
Section: Certain Conditions Affectingmentioning
confidence: 95%
“…There is an extensive list of diseases that will result in decreased intake or increased energy requirements including but not limited to dental and oral cavity diseases, gastric ulcers, enteritis, colitis, peritonitis, liver disease, pneumonia, pleuritis, dysphagia, endocrinopathies and sepsis . Regardless of the inciting cause, if long‐lasting, negative energy and nitrogen balance will lead to weight loss, muscle loss, lipid mobilisation, a decrease in immune system competence and prolongation of recovery from illnesses due to decrease in efficacy of therapeutic interventions; ultimately resulting in an increased cost or even poorer prognosis . During feed deprivation, the metabolic rate, thyroxin synthesis and glycogen stores decrease .…”
Section: Introductionmentioning
confidence: 99%
“…We chose noise as a model of stress because the effect of noise on the immune responses have never been studied in humans, whatever the age, and the first results obtained in young mice (8)(9)(10) suggested that this model could be particularly relevant to the study of the influence of stress on macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies that have examined the relationship between stress and immunity have dealt with the effects of stress on lymphocytes or NK cells of adult humans or experimental animals (1)(2)(3)(4)(5). Only a few, however, have explored the association between stress and macrophage function (6,7), and still fewer, the effects of stress on the immune response of old animals or humans (8)(9)(10). Moreover, most experimental studies have used acute or chronic stresses that are not encountered by humans in daily life, such as electric shock, cold water immersion or water deprivation.…”
Section: Introductionmentioning
confidence: 99%